The Study of Mass Transfer Coefficient in Membrane Separation for Produced Water - Khor, Ee Huey; Samyudia, Yudi (Engineers Australia, 2009)
In this paper, membrane filtration of produced water is studied in terms of its mass transfer coefficient. This filtration process is incorporated to improve the existing OSPAR method in removing dissolved oil. During membrane filtration, concentration nearer to the membrane is higher than the concentration of bulk solution and thus a concentration profile develops. Studying the mass transfer coefficient (MTC) which drives the concentration difference can help us in understanding the phenomena of fouling in membrane. Two models i.e. combined solution diffusion/film theory model (Murthy and Gupta, 1997) and film theory model are compared and the most suitable model to predict the MTC is selected. From the experimental results, it was found that film theory (FT) model is suitable to calculate MTC for produced water samples in our experimental set-up. The models are found to be suitable only at a certain range of differential pressure.